Evidenciação de práticas de governança pública em relatórios de gestão: um estudo nas universidades federais brasileiras - Borges, Gerlyson Girão (2024)
Public governance is an effective tool for improving the organizational performance of Brazilian federal universities. There is a low numbers of studies on the subject in Brazil. This research aimed to analyze the disclosure of public governance practices in the management reports of Brazilian federal universities. This is a qualitative study that used content analysis of management reports for 2021, using Atlas.ti software version 23 and then compared the resulting level of governance with the iGovPub governance assessment index presented by the Federal Court of Auditors. The results made it possible to identify the main public governance practices adopted according to leadership, strategy and control mechanisms. The individual situation of the institutions was verified and the average results obtained by the regional groups of universities were compared. They were classified as having medium disclosure for the governance mechanisms, except for the group from the North and Southeast regions, which were classified as having high disclosure for the control mechanism. A good alignment a good alignment was identified between the level of adoption of governance practices identified in this research and index iGovPub was verified, governance assessment presented by the Federal Court of Accounts for those 53 universities whose comparative data was available during the period analyzed. It can be identified that some federal universities have shown advanced adoption of public governance, but that most of them still need to strengthen these arrangements. This study contributes to identify points for improvement, both in terms of disclosure and the actual practice of governance mechanisms in Brazilian federal universities.